Overview of Protein and Fe Intake With The Event of Anemia In Adolescent: Systematic Review - Erningtyas, Cantika; Amalia, Rize Budi; Faizah, Zakiyatul (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Adolescents are a group that is prone to anemia. Anemia is defined as a lower than normal haemoglobin level. The prevalence of anemia in adolescents in Indonesia is the highest at the age group of 15-24 years, 32%. The most common cause of anemia is lack of nutrients needed for erythrocyte synthesis. Substances that play a role in haemolysis are protein, vitamins (folic acid, vitamin B12, vitamin C and vitamin E), and minerals (Fe and Cu). Objective: To analyse the intake of protein and iron expected incidence of anemia in adolescent girls. Methods: This study used a systematic review method. The databases used to conduct this research are Scopus, PubMed, Science Direct, Portal Garuda and Google Scholar. The keywords used in Indonesian are "Anemia", "Remaja", "Asupan Gizi" or "Nutrisi", "Protein", "Fe" or "Zat besi" and in English are "Anemia", "Adolescent", “Nutritional Intake”, “Ferrous Sulfate” OR “Protein” Results: From several articles that have been reviewed, it is shown that protein intake and Fe (iron) intake of adolescents related to anemia are associated with the incidence of anemia experienced by adolescents. A good protein intake will affect haemoglobin levels in adolescent girls. In addition, intake of Fe (iron) will also affect haemoglobin levels in adolescents. Conclusion: intake of protein and iron will affect haemoglobin levels in adolescents.